PENGARUH PADAT TEBAR YANG BERBEDA TERHADAP PERTUMBUHAN IKAN SELAIS (Kryptopterus lais) DALAM KERAMBA JARING APUNG DI TASIK BETUNG KABUPATEN SIAK PROVINSI RIAU - Agusnimar Agusnimar; Rosyadi Rosyadi; Vicky Renaldo Anggi (UIR Press, 2014)
A study on the effect of stocking density toward growth rate of selais fish (Kryptopterus lais) was conducted in Betung lake, located in core zone of biosphere reserve of Giam Siak Kecil Bukit Batu, Riau Province from 1th May – 30 June 2011. The objective of the study was to determine the effect of the stocking density on the growth of selais fish reared in floating cages that placed into the Betung lake. The research used completely randomsize design experimental method with thee treatments of density and three replications. There were 10 fish/m³, 20 fish/m³ and 30 fish/m³. The seed of fish were placed into cages (1 m x 1 m x 1.2 m) and reared for 60 days. Commercial feed was given three times a day with 33% of protein. The result showed that stocking density had a significant effect on growth rate of K. lais. The best stock density was 10 fish/m³ and giving highest growth rate and daily growth rapid of selais fish, namely 23.7 gr and 2.55 %, respectively.